Quaternary environmental change off northwest Svalbard - Gauti Trygvason Eliassen 1988- (2013)
In 2005 the piston core JM05-030-PC2 was collected from the northwest continental slope of Svalbard, approx. 100km of the nortwest coast at water depths of 1073m. At the study site, the oceanographic system is dominated by two main currents; the East Greenland Current and the West Spitsbergen Current. The East Greenland Current tranports cold and fresh polar water, and is the main transporter of sea-ice into the Atlantic Ocean. The West Spitsbergen Current is the northernmost limb of the North Atlantic Current, and is the main transporter of heat into the Arctic Ocean. Thus this area is sensitive to changes in oceanographic and climatic conditions. The object was to investigate past environmental and climate changes during the Quaternary Period. To achieve this goal a multi-proxy analyses was performed. The studied interval is from 500cm to 600cm depth in core. The methods used were; Lithological logging, magnetic susceptibility, shear strength analysis, water content and granulometry analysis, IRD (Ice Rafted Detritus) count, as well as foraminifera analyses were applied to the studied interval. The results indicate a colder climate than at present. The studied interval of the core is thought to represent ages from approximately 27,500 cal years BP to 21,250 cal years BP. The oldest part of the studied interval shows evidence of seasonal sea-ice and iceberg melting over the site, while the youngest (top) part of the studied interval is indicative of possible perennial sea-ice cover. A debris flow unit towards the top of the core might indicate peak glaciation of the northwestern Svalbard continental shelf. Down-slope movement of sediments are most active during full glaciation of the shelf area. When compared to previously published data; IRD concentration, lithology, magnetic susceptibility, and the general lack of foraminifera in the top of the core point to a depositional timing of the Last Glacial Maximum. Árið 2005 var stimpil kjarninn JM05-030-PC2 tekinn úr norðvestur landgrunnshlíð Svalbarða á 1073m ...